Teaching the Interpretation of a Literary Text in German Lessons - Mansurova Gulbahor Makhdievna (Genius Journals, 2022)
The paper attempts to consider approaches to teaching a foreign language on the basis of a literary text, developing the creative abilities of students, shaping their readiness to engage in a dialogue of cultures and planning their speech and non-speech behavior, improve semantic reading skills, develop research skills and communicative competence.
Keywords: Literary texts; foreign language; linguistic and sociocultural experience; communicative competence